Web-Based Decision Support System For Selecting The Best Field Work Practice Placement Using The Topsis Method - Dimas Ahsanul Habibi Dimas; Eri Zuliarso; Eka Ardhianto (CV. AFDIFAL MAJU BERKAH, 2026)
The selection of an optimal internship placement represents a significant challenge for students and schools due to the large number of partner companies available and the diversity of evaluation criteria involved. This study develops a Decision Support System (DSS) to determine the best internship placement using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. The system was developed using PHP and MySQL technologies and is accessible through a web browser to facilitate user access and interaction. The study utilized data from 10 internship partner companies of SMK Islam Nusantara Comal in 2024, evaluated based on five criteria: distance, position quota, field suitability, facilities, and company reputation. The calculation results indicate that PT Laksana Manufacturing ranked first with a preference value of 0.7884. The developed system proved effective in supporting objective and efficient decision-making processes.